STUDY ON THE NATURE AND STATUS OF AIR QUALITY OF GOPALGANJ DISTRICT WITH REFERENCE TO RESIDENTIAL AREAS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Indoor air pollutants can originate within the building or be drawn in from outdoors. Air contaminants consist of numerous particulates, fibers, mists, bio aerosols, and gases. In addition, another complicating factor is that indoor air pollutant concentration levels can vary by time and location with sensitive environments of college. Pollutants can emit from variety of sources, related to building or around the buildings. A number of studies have revealed that college air may be a source of a wide spectrum of air pollutants, such as noise, NO2, CO, volatile organic compounds, aerosols. The highest importance is currently attributed to aerosols because they represent a complex mixture of organic and inorganic substances with potential toxic, carcinogenic, inflammatory, allergenic, and other adverse properties. Indoor air quality is affected by outdoor pollution from traffic, industrial construction, and combustion activities, but also by ventilation, furnishings, and the indoor activities of occupants.